2015
DOI: 10.3109/01942638.2015.1040572
|View full text |Cite
|
Sign up to set email alerts
|

Using Multitouch Collaboration Technology to Enhance Social Interaction of Children with High-Functioning Autism

Abstract: These findings provide support for the use of collaborative technology-based interventions within educational settings to enhance social interaction of children with HFASD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
1
10

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 26 publications
1
30
1
10
Order By: Relevance
“…On average, we found 4.8 (SD=2.5), 5.5 (SD=3.5), and 6.6 (SD=2.8) WA information exchanges in the private, task-dependent, and public modes, respectively. We did not find a significant main effect of either feedback mode (F (2,18) of WA information exchanges. However, we did find a significant interaction between factors (F(2,18)=4.489, p<.05), suggesting that the public feedback mode is more sensitive to distractors than private mode (F(2,18)=7.573, p<.05), increasing total information exchanges.…”
Section: Workpace Awareness Information Exchangescontrasting
confidence: 79%
See 2 more Smart Citations
“…On average, we found 4.8 (SD=2.5), 5.5 (SD=3.5), and 6.6 (SD=2.8) WA information exchanges in the private, task-dependent, and public modes, respectively. We did not find a significant main effect of either feedback mode (F (2,18) of WA information exchanges. However, we did find a significant interaction between factors (F(2,18)=4.489, p<.05), suggesting that the public feedback mode is more sensitive to distractors than private mode (F(2,18)=7.573, p<.05), increasing total information exchanges.…”
Section: Workpace Awareness Information Exchangescontrasting
confidence: 79%
“…In the past decade, interactive tabletops have been successfully used in multiple domains, including healthcare, education, entertainment, and cultural exhibitions [2,18,34,36]. These devices show significant advantages in supporting multi-user interaction, namely due to their large shared surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of studies have demonstrated significant improvements in the social interaction, communication and conversation skills of children with ASD after playing SGs [6][7][8][9]. For instance, PixTalk [8] is a smart phone application, with many pictures designed to help children express their feelings and emotions by browsing and selecting images.…”
Section: Purpose Of Serious Games For Children With Asdmentioning
confidence: 99%
“…Over the past several years, a number of collaborative technology-enabled training applications emerged to provide a safer, affordable, and repetitive environment for children with ASD (Chen, 2012; Kientz, Goodwin, Hayes, & Abowd, 2013; Millen et al., 2011). Among them, collaborative games have gained prominence to train children joint attention skills (e.g., Battocchi et al., 2009; Boyle, Arnedillo-Sanchez, & Zahid, 2015; Gal, Lamash, Bauminger-Zviely, Zancanaro, & Weiss, 2016; Giusti, Zancanaro, Gal, & Weiss, 2011; Goh, Shou, Tan, & Lum, 2012; Millen et al., 2011; Piper, O’Brien, Morris, & Winograd, 2006; Rehg et al., 2013), mainly due to its inherent multiuser features to promote and facilitate collaborative work and information sharing (Edward, Greenberg, Shen, & Forlines, 2007; Silva et al., 2015). However, the majority of these games are often developed to enhance children’s social communication skills and promote cooperative works (Battocchi et al., 2009; Ben-Sasson et al., 2013; Boyle et al., 2015; Gal et al., 2016; Giusti et al., 2011; Goh et al., 2012; Hourcade, Bullock-Rest, & Hansen, 2012; Millen et al., 2011; Rehg et al., 2013; Silva et al., 2015); as such, these applications contain only one workspace where collaboration is tightly coupled (Battocchi et al., 2009; Giusti et al., 2011; Piper et al., 2006).…”
Section: Introductionmentioning
confidence: 99%